Cathepsins in oral diseases: mechanisms and therapeutic implications - Jiang, Hao; Dong, Zuoxiang; Xia, Xiaomin; Li, Xue (Frontiers in Immunology, 2023)
Cathepsins are a type of lysosomal globulin hydrolase and are crucial for many physiological processes, including the resorption of bone matrix, innate immunity, apoptosis, proliferation, metastasis, autophagy, and angiogenesis. Findings regarding their functions in human physiological processes and disorders have drawn extensive attention. In this review, we will focus on the relationship between cathepsins and oral diseases. We highlight the structural and functional properties of cathepsins related to oral diseases, as well as the regulatory mechanisms in tissue and cells and their therapeutic uses. Elucidating the associated mechanism between cathepsins and oral diseases is thought to be a promising strategy for the treatment of oral diseases and may be a starting point for further studies at the molecular level.